HIV-1 Vif: a guardian of the virus that opens up a new era in the research field of restriction factors - Takaori-Kondo, Akifumi; Shindo, Keisuke (Frontiers in Microbiology, 2013)
The research on Vif protein had started in late 80s right after HIV-1 was cloned, and the function of Vif had been a mystery for a long time. However, the research on Vif has finally lead to the identification of APOBEC3G, which opens up the new era in the research field of host restriction factors in HIV-1 infection followed by TRIM5α, Tetherin/BST-2, and SAMHD1. This suggests that continuation of basic research on fundamental questions is quite important. We still have many questions on Vif and APOBEC3 and should continue to work on these proteins in the future in order to better regulate HIV-1. We will discuss about not only the history but also recent advances on Vif research.